2019
DOI: 10.1016/j.scs.2019.101467
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of a solar thermal system in Spain, eco-design alternatives and derived climate change scenarios at Spanish and Chinese National levels

Abstract: Solar thermal energy is considered a 'clean' form of energy; however, environmental impacts occur during its life-cycle. The present work compares the environmental performance of two scenarios: a solar thermal system for providing domestic hot water (DHW) used in conjunction with a traditional natural gas heating system, and the natural gas heating system on its own. Weak points are found and different eco-design scenarios are evaluated in order to achieve a more circular economy. In addition, the authors exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Indeed, from literature some data about the use of Electricity and Natural Gas Systems (NGS) for domestic heating were also collected: from Martinopolous et al emerged a value of 1.41 kg CO2-eq /kWh if the thermal load is entirely covered by electricity, using country specific data for electricity production in Greece (Martinopoulos et al, 2013) and Pratiwi reported a value of Bayer et al of 1.18 kg CO2-eq /kWh as electricity mix average carbon emission in Poland (Bayer et al, 2013;Pratiwi and Trutnevyte, 2020). Moreover, Albertì et al reported 0.264 kg CO2-eq /kWh for domestic hot water production from NGS (Albertí et al, 2019).…”
Section: Data Comparison and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, from literature some data about the use of Electricity and Natural Gas Systems (NGS) for domestic heating were also collected: from Martinopolous et al emerged a value of 1.41 kg CO2-eq /kWh if the thermal load is entirely covered by electricity, using country specific data for electricity production in Greece (Martinopoulos et al, 2013) and Pratiwi reported a value of Bayer et al of 1.18 kg CO2-eq /kWh as electricity mix average carbon emission in Poland (Bayer et al, 2013;Pratiwi and Trutnevyte, 2020). Moreover, Albertì et al reported 0.264 kg CO2-eq /kWh for domestic hot water production from NGS (Albertí et al, 2019).…”
Section: Data Comparison and Discussionmentioning
confidence: 99%
“…Having the total thermal load expressed in kWh and the total emissions expressed in kg CO2-eq , the values were expressed in kg CO2-eq /kWh. Albertí et al (2019) directly reported the values of the Global Warming impact in kg CO2 . All of the other cited studies (Frick et al, 2010;Karlsdottir et al, 2014;Lacirignola and Blanc, 2013;Pratiwi et al, 2018;Trutnevyte, 2020, 2021) reported the values of the Global Warming impact in kg CO2-eq /MWh so the values were just expressed in kg CO2-eq /kWh.…”
Section: Literature Data Collection and Screening Approachmentioning
confidence: 99%
“…Also, the materials used in product assembly, which accounted for less than 1% of the weight of solar panels, were left out of this analysis. The DHWSs were estimated to have a 10-year life cycle even if there are working systems that are 20 years old, (Albertí et al, 2019).…”
Section: Lca For Solar Thermal Collectorsmentioning
confidence: 99%
“…(Hang et al, 2012) carried out a comparative LCA of thermal solar systems focused exclusively on the analysis of flat plate collectors and vacuum tubes. Other authors (Albertí et al, 2019;de Laborderie et al, 2011) compare the environmental performance of solar thermal system for providing DHW used in conjunction with complementary heating systems and more conventional scenarios providing the same service (as natural gas heating system). The CSHPSS technology is an environmentally and sustainable and feasible option, both in warm and Mediterranean climates (Tulus et al, 2016) and in coldest regions (Welsch et al, 2018), where district heating should be featured prominently among other options.…”
Section: Introductionmentioning
confidence: 99%